Effectivity of hand washing technique using World Health Organization (WHO) method with an ultraviolet light assessment on health workers at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara February-March 2018 - Olivia A. Hanafiah; Isnandar Isnandar; Indra B. Siregar; Lung L. Wong (DiscoverSys Inc., 2019)
Objective: This study aim to determine the effectivity of hand washing technique using the World Health Organization (WHO) method with Ultraviolet Light Assessment on health workers at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas of Sumatera Utara February-March 2018.Material and Methods: This study was an experimental study with a one group pre-test post-test group design. The sampling method used in this study was purposive sampling. 18 undergraduate students in the Department of Oral and Maxillofacial Surgery participated as subjects of this study. Sample was assessed before and after hand washing using WHO method.Results: Hand washing technique using WHO method was effective on the palm, back of hands, between fingers, and thumbs (p<0.05) while on fingertips was not effective (p>0.05).Conclusion: Effectivity of hand washing technique using WHO method with the Ultraviolet Light Assessment on health workers at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara February – March 2018 was effective.